2021
DOI: 10.7759/cureus.18095
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Gamma Knife Radiosurgery for Glomus Tumors: An Analysis of 32 Patients

Abstract: BackgroundGlomus jugulare tumors are rare slow-growing hypervascular tumors that arise from the paraganglia of the chemoreceptor system within the jugulare foramen of the temporal lobe. The historical standard treatment has been surgical resection, but because of their high vascularity and involvement with cranial nerves (CNs), Gamma Knife radiosurgery (GKRS) has been advocated as an alternative. The goal of this study is to update and report long-term results of GKRS to achieve local control and symptomatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Regarding the complications reported, considering the total number of studies included, 18 cases of hearing impairment were reported;[ 3 , 5 , 8 , 13 , 25 ] six cases of vertigo;[ 20 , 25 , 31 ] five cases of transient facial paralysis;[ 5 , 9 , 16 , 18 , 25 ] four cases of vocal cord paralysis;[ 17 , 18 , 31 ] three cases of headache;[ 3 , 22 , 30 ] two cases of dysphagia;[ 31 ] two cases of transitory taste disturbance;[ 31 ] a case of transient ataxia;[ 20 ] one case of diplopia;[ 30 ] and one case of development of non-viable tissue within the medial external auditory canal that required debridement. [ 31 ] No cases of mortality attributable to treatment were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the complications reported, considering the total number of studies included, 18 cases of hearing impairment were reported;[ 3 , 5 , 8 , 13 , 25 ] six cases of vertigo;[ 20 , 25 , 31 ] five cases of transient facial paralysis;[ 5 , 9 , 16 , 18 , 25 ] four cases of vocal cord paralysis;[ 17 , 18 , 31 ] three cases of headache;[ 3 , 22 , 30 ] two cases of dysphagia;[ 31 ] two cases of transitory taste disturbance;[ 31 ] a case of transient ataxia;[ 20 ] one case of diplopia;[ 30 ] and one case of development of non-viable tissue within the medial external auditory canal that required debridement. [ 31 ] No cases of mortality attributable to treatment were reported.…”
Section: Resultsmentioning
confidence: 99%
“…All GJTs are highly vascular and develop within proximity to the pars nervosa of the jugular foramen, rendering gross-total resection (GTR) challenging with a relatively high risk of lower cranial nerve injury. [1,3] Thus, it is not surprising that resection entails a great deal of morbidity and often leaves behind large residual tumors and even may cause mortality [1,4,7,14,15,16 ].…”
Section: Introductionmentioning
confidence: 99%
“…summarizing the data and outcome of these series [1,2,6,8,10,11,12,14,15,17,24,[31][32][33][34][35][36][37][38]. …”
mentioning
confidence: 99%